Prevalence and factors associated with Anemia among Pregnant Women attending Antenatal Care at Mpigi Health Centre IV. A Cross-sectional study. - Mpaulo , Stephen (Student's Journal of Health Research Africa, 2022)
Background: Anemia continues to be a challenging condition and a common condition among many mothers attending antenatal clinics in many hospitals in Uganda. The aim was to ascertain the proportion and factors associated with anemia among pregnant women in Mpigi Health Center IV which serves as a District hospital in Mpigi District. Methodology: A cross-sectional study was done in which both qualitative and quantitative research designs were used. 100 respondents were chosen to take part in the study. The data was collected between December 2021 and January 2022 Results: The study found that the prevalence of Anemia was low. It showed that about 24% and those that presented with mild anemia were 75%. The major risk factors included multiparity, multi gravidity, helminths infections, low standards of living, and poor diet among others. Recommendation: After a study, the researcher recommends continuous health education to mothers on the dangers of anemia and its prevention. This could be done majorly during antennal care sessions, continuous deworming during antenatal visits would help to reduce the anemia which is due to infestation with helminth infections. Conclusion: Having a well-balanced diet would be good advice as it would greatly reduce the risk of contracting anemia, especially iron-deficiency anemia. This would also require a multisectoral approach were nutritionists, health workers, and the community would be put together to reduce or eliminate anemia in the community among pregnant women.